Efficiency of use of the “artp” learning style in significant learning - Sotomayor-Herrera, Fredi (2020)
The research work aimed to: determine the degree of effectiveness of the "ARTP" Program in Meaningful Learning in the Area of ​​Personal Development Citizenship and Civics of students at the secondary level of the Private Integrated Educational Institution San Vicente de la Barquera de Huánuco - 2019, for this, the experimental causi design was used with pretest and posttest; The sample consisted of a total of 52 students, divided into two sections: "A" and "B"; both with 26 students respectively; the first represents the experimental group and the second the control group. A questionnaire (pretest) was applied to both groups, then the respective treatment was made only to the experimental group and finally a questionnaire (posttest) was applied to both groups, in this way the effectiveness of the ARTP Program in the Significant Learning of the students. Regarding research methods, both logical methods (deductive, inductive, analytical - synthetic) and empirical methods (observation and experimentation) were used. The "ARTP" Program improves the Level of Significant Learning in the Area of ​​Personal Development Citizenship and Civics of students at the secondary level of the Private Integrated Educational Institution San Vicente de la Barquera de Huánuco -2019, as evidenced by the percentages obtained. There is a significant correlation of 0.69 between the variables: ARTP Program and Significant Learning; which is very positive from all points of view, since the hypothesis is validated.